Medical perspectives on talent development in youth sports - John, T.; Carter, C. W. (Routledge handbook of talent identification and development in sport, 2017)
While much attention is paid to the identification and cultivation of athletic talent in children and adolescents, it is essential to remember that the benefits of youth talent development are only realized if young athletes are able to stay healthy and injury-free as they mature and develop. Having a basic understanding of the specific risks of injury and illness that young athletes face is critical to ensuring their continued health, optimal performance, and athletic longevity. The primary goal of health care providers who interact with young athletes is therefore to protect talent by identifying those young athletes at risk for sports-related injuries—both acute and chronic— and taking steps to mitigate or avoid entirely the impact that such injuries may ultimately have on present and future athletic performance.